(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
This research paper is an effort to use those materials which are disposed as wastes for stabilizing the soil and making the process cost effective. In this research work, two waste materials such as Red Mud and Hydrated Lime is used in different percentages. Hydrated lime (HL) is blended with the natural sample of soil in the proportion of (0%, 2%, 4%, 6%, 8%, and 10%) by weight of soil. 6% Hydrated lime was taken as an optimum proportion depending on UCS values. The UCS value of natural soil showed an increment from 89.5KN/m2 to 120.6 KN/m2 when 6% HL was blended with the natural soil. This value showed further an increment when the Soil+6% HL mix was cured. The UCS value raised to 192.3 KN/m2and 242.23 KN/m2 when cured for a period of 7 and 28 days respectively. Then RM was added in different proportion (5%, 10%, 15% and 20%) to Soil+ 6% HL mix. It was revealed from results that the UCS attained a maximum value of 235.6 KN/m2 at the addition of 6% HL and 15% RM to the natural soil. This value further showed an improvement to 279.4KN/m2, 307.4KN/m2 and 316.7 KN/m2 when the sample was cured for 7 and 28 days respectively.